Airline cooperation effects on airfare distribution: An auction-model-based approach. (January 2022) - Ivaldi, Marc; Petrova, Milena; Urdanoz, Miguel
Abstract: Airline alliances have a long history yet there is no academic consensus on how they affect price levels and their impact on price dispersion has not yet been studied. We address this question using a novel methodology motivated by the service homogenization and increased price competition in this industry in the recent years. Establishing an equivalence between the online sales process and a reverse English auction, we use methods from auction econometrics to work in a new way with the standard industry data set: using individual ticket sales where only aggregated prices have been used in the past. Applicable to other industries where sellers compete in prices, this approach allows us to reconsider the effect of airline alliances on the distribution of airfares in the US domestic market. We find lower price mean and dispersion in markets where airlines belong to an alliance as a result of the lower variability of costs. The methodology we apply here can be used to study any distribution of individualized prices, which are now prevalent since the advent of the digital economy. Highlights: This is the first work to study the impact of alliances on price dispersion. The applied methodology allows to study jointly the average and standard deviation of prices and reservation costs. Airline Alliances decreased prices and price dispersion on the US domestic duopoly markets. Airline Alliances decreased the dispersion of reservation costs on the US domestic duopoly markets. This is the first article to apply auction theory and econometrics of auctions to air ticket sales.